The effect of carbon and polypropylene fibers on thermal shock resistance of the refractory castable - Antonovič, Valentin; Witek, Jerzy; Mačiulaitis, Romualdas; Boris, Renata; Stonys, Rimvydas (Journal of Civil Engineering and Management, 2017)
This work investigates medium cement refractory castable with additives of carbon and polypropylene fibers. The peculiarities of microstructure changes in the fiber and castable matrix contact zone, channel formation, and changes of cold crushing strength of fiber additives, which have a refractory castable matrix under temperature treatment, were investigated. The investigation results allowed to predict that using a mix of fibers more effective than using them individually. The influence of fiber additives on the mechanical characteristics and thermal shock resistance of the refractory castable with fiber additives was tested. It was found that the addition of carbon fiber has a positive impact on the thermal shock resistance of the investigated castable, which is confirmed by the results obtained by thermal cycling, as well as by the values calculated for thermal shock resistance R4 and Rst. In addition, the results of the investigation of thermal cycling show that the value of the thermal shock resistance was highest when a mixed fiber additive (CF+PP) was used.